The Analysis Of Voltage Optimization System With Pararel Series Arranger In Solar Cell - Ibrahim Ashari; Ahmad Faisol (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2020)
Parallel series is very suitable to be used to overcome the ups and down of voltage caused by the supply of sunlight to the solar cell. The series circuit can be used to overcome the lack of voltage on the solar cell, while the parallel circuit is used to flow larger currents with a constant voltage when the supply of sunlight on the solar cell is at its maximum. Solar cell as converters of sunlight into electrical energy in the form of DC voltages, which are connected in parallel series by utilizing relay contacts that are controlled using atmega 16 microcontroller, where the voltage generated by the solar cell in the sensor uses a voltage sensor. Switching regulator as lowering the voltage over solar cell for battery charging. The test results using a series of series and minimum lighting produces a voltage 14,8 Volt, parallel circuits and maximum lighting produces a voltage of 20 volts, and a combination of parallel-series under moderate lighting conditions produces a voltage of 23.3 VoltDOI : https://doi.org/10.26905/jeemecs.v3i2.4731